Strategi Kreatif Iklan Kartu Kredit (Studi Kasus Iklan Kartu Kredit Bank BNI, Bank Mandiri, dan Bank BCA) - Darfi Riskavirwan; Agung Eko Budiwaspada (Wimba : Jurnal Komunikasi Visual, 2011)
Credit card becomes one of the popular banking transaction media. One of the facts is that nowadays credit cards are used in most product and service businesses. Another fact is that credit cards can accommodate their user's lifestyle and shopping habit. In fact, in Indonesia the credit card advertisements have been so abundant that they give an impression of the aggressiveness of the companies producing them and the an impression that it is easy to get the advertised credit cards. Each established bank like BNI, BCA, and Mandiri has its own way of advertising its credit card. It was found that the three banks used each own creative strategy to market or advertise its own credit card and its other credit card-like products.The purpose of this research to see the similarities among the three banks' credit cards and among their other credit card-like products, both of which were the subjects of this study. The methodology used in this study is juxtaposition one. In addition, the approach employed was semiotics. The latter was used to analyze the message construction in each visual advertisement, particularly in its message meaning and visual sign. Since both the semiotics and creative strategy approach are not adequate to analyze the message construction, the interdisciplinary approach was used. Therefore, advertising, message, and persuasive psychology theory were employed in this study. The advertising theory was used to analyze the anatomy, type, and display of advertisement. As for the message theory, it was used to analyze both the message delivery techniques and the message styles that were used in the advertisements. As to the persuasive psychology, it was used to analyze the method each credit card advertisement employed in persuading its target audience.The analyses shows that the credit cards of the three banks shared some similarities and differences as far as the creative strategy is concerned. One of the similarities is that they tend to use emotional strategy in their advertisements although each bank, in fact, use different emotional strategy approach. BNI bank tends to use psychological approach in its creative strategy; Mandiri Bank tends to use psychological and sociological approach equally; and BCA bank tends to use sociological approach thoroughly in its creative strategy.